2023
DOI: 10.1007/s13402-023-00821-w
|View full text |Cite
|
Sign up to set email alerts
|

MAOA suppresses the growth of gastric cancer by interacting with NDRG1 and regulating the Warburg effect through the PI3K/AKT/mTOR pathway

Abstract: ObjectivePrevious studies have indicated that neurotransmitters play important roles in the occurrence and development of gastric cancer. MAOA is an important catecholamine neurotransmitter-degrading enzyme involvedin the degradation of norepinephrine, epinephrine and serotonin. To nd a potential therapeutic target for the treatment of gastric cancer, the biological functions of MAOA and the underlying mechanism in gastric cancer need to be explored. MethodsThe Cancer Genome Atlas(TCGA), Gene Expression Omnibu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Abnormalities of the PI3K/AKT/mTOR pathway are observed in the majority of malignancies including GC, and participate in diverse physiological processes such as cell proliferation, metastasis, and chemoresistance. 20,21 Notably, the PI3K/AKT/ mTOR pathway was able to promote the carcinogenesis of GC by increasing post-translational phosphorylation. 22 Additionally, our previous study showed that G6PC facilitated the advancement of cervical cancer by activating the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities of the PI3K/AKT/mTOR pathway are observed in the majority of malignancies including GC, and participate in diverse physiological processes such as cell proliferation, metastasis, and chemoresistance. 20,21 Notably, the PI3K/AKT/ mTOR pathway was able to promote the carcinogenesis of GC by increasing post-translational phosphorylation. 22 Additionally, our previous study showed that G6PC facilitated the advancement of cervical cancer by activating the PI3K/AKT/mTOR signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT signaling pathway can be abnormally activated in most cancers, promoting tumor cell proliferation, inhibiting apoptosis, and enhancing invasion and metastasis[ 25 ]. Wang et al [ 26 ] verified that monoamine oxidase A inhibits the progression of GC by reducing glycolysis through the PI3K/Akt/mTOR pathway. Inhibition of the PI3K/Akt pathway may provide a potential method for GC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not delve into the molecular mechanisms of MAOA in gastric cancer development or consider its expression in gastric cancer tissues for clinical relevance. Another study mentioned that MAOA can interact with NDRG1, inhibiting downstream PI3K/AKT/mTOR pathway activity, thereby attenuating the Warburg effect in gastric cancer cells and ultimately suppressing tumor cell proliferation and malignant behavior [ 9 ]. These conflicting results warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in cancer-related research, the release of 5-HT has been associated with tumor progression, and 5-HT acts as a growth factor for prostate cancer (PCa) cells [ 5 ]. Furthermore, elevated MAOA expression is linked to high-grade PCa and contributes to a poorly differentiated phenotype [ 6 9 ]. Studies have also indicated that MAOA expression is significantly downregulated in gastric cancer tissue.…”
Section: Introductionmentioning
confidence: 99%